Women’s representation and environmental sustainability in the Niger Delta: a critique of two Nigerian novels (2022)
This article examines the discourse of environmental degradation in the Niger Delta region with a focus on the representation of women and their roles in environmental renaissance and sustainability in the Niger Delta. Women have traditionally been portrayed as victims of environmental degradation in contemporary Nigerian fiction. The objective of this article is to deconstruct the perception of female victimology by investigating the roles women in environmental sustainability, ecological regeneration and the development of African societies, especially in the Niger Delta. This article therefore attempts to foreground firm resolutions of women characters in May Ifeoma Nwoye’s Oil cemetery and Vincent Egbuson’s Love my planet in relation to human and environmental regeneration. This study employs eco-feminism, an aspect of Eco-criticism, to critique issues of women and environmental sustainability arising in the Niger Delta environment, their awareness of and responses to the ecological damage in the region.